Peran Kegiatan Bina Mental Tausiyah Jum’at dalam Meningkatkan Kedisiplinan dan Kecerdasan Spritual Siswa - Nursela Anggraini; Zul Azhar; Syahril Hasibuan; Herlinawati Herlinawati (Mathematics Education Study Program, 2025)
This study aims to examine the role of Friday Tausiyah Mental Development activities in improving student discipline and spiritual intelligence. The focus of the study in this research on three things, namely the role of Friday tausiyah mental development activities on the formation of student discipline and spiritual intelligence, obstacles / obstacles faced in the implementation of Friday tausiyah mental development activities in improving student discipline and spiritual intelligence, and solutions in overcoming obstacles in the implementation of Friday tausiyah mental development activities. The research method used is phenomenology-based qualitative. The data collection techniques used were observation, interviews, and documentation studies. The data obtained were then analyzed using the Miles and Huberman technique, namely data reduction, data display, and conclusion drawing. The results of the study explain that this activity plays a significant role in increasing students' awareness of the importance of discipline, forming good habits, increasing students' sense of responsibility, and helping to develop students' talents. This Friday Tausiyah Mental Development activity faces obstacles such as lack of consistency in student participation, schedule clashes, differences in understanding, and perceptions of monotony. Proposed solutions include increasing students' understanding of the benefits of tausiyah, adjusting schedules, presenting relevant material, and using more varied and interactive delivery methods to increase participation and activity effectiveness. This research makes an important contribution in understanding how religious activities can support the development of students' character and spirituality in an educational setting.